Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41598-017-09298-8
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and evolutionary consequences of alternative sex-change pathways in fish

Abstract: Sequentially hermaphroditic fish change sex from male to female (protandry) or vice versa (protogyny), increasing their fitness by becoming highly fecund females or large dominant males, respectively. These life-history strategies present different social organizations and reproductive modes, from near-random mating in protandry, to aggregate- and harem-spawning in protogyny. Using a combination of theoretical and molecular approaches, we compared variance in reproductive success (V k*) and effective populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 64 publications
1
43
0
Order By: Relevance
“…Indeed, we often tend to oversimplify the complexity of sequential hermaphroditism: not all protogynous species are haremic, as not all protandrous species mate in pairs. A recent study 28,85 has revealed a broader variation in effective population size in protogynous species that differs from the more limited expectations obtained when all protogynous species were considered haremic by default. Instead, some protogynous species were found to be group spawners, altering the expectations that all protogynous species should have low effective population size due to their supposed haremic system.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, we often tend to oversimplify the complexity of sequential hermaphroditism: not all protogynous species are haremic, as not all protandrous species mate in pairs. A recent study 28,85 has revealed a broader variation in effective population size in protogynous species that differs from the more limited expectations obtained when all protogynous species were considered haremic by default. Instead, some protogynous species were found to be group spawners, altering the expectations that all protogynous species should have low effective population size due to their supposed haremic system.…”
Section: Discussionmentioning
confidence: 82%
“…The prediction column summarizes the overall expectation on sperm competition (and thus GSI) for the sexual system, based on the most common mating and spawning mode, according to the SAM 23,24 . *Protogynous group spawners should be favoured as large males can produce more sperm 28 . **Promiscuous large groups are not common, but still present in protandrous species (see text for examples).…”
Section: Methodsmentioning
confidence: 99%
“…The above model assumes a single, knife-edge age at which all surviving individuals change sex. In real populations, the distribution of sex ratio over time is typically sigmoidal [7]:…”
Section: (A) Ess Theorymentioning
confidence: 99%
“…Sex reversal is found in over a dozen invertebrate phyla, including corals, sponges, molluscs, annelids, echinoderms and (alone among arthropods) crustaceans; in plants, simultaneous hermaphrodites are more common, but species that change sex occur in all major groups [1][2][3]. Among vertebrates, this strategy is restricted to teleost fishes, but within that group it occurs in at least 27 families [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation